Acute kidney injury in hospitalized patients with methanol intoxication: National Inpatient Sample 2003-2014 - Charat Thongprayoon (2022)
BACKGROUND: This study aimed to 1) determine the incidence of acute kidney injury (AKI), 2) identify risk factors for AKI, and 3) evaluate the impact of AKI on in-hospital outcomes in hospitalized patients for methanol intoxication. METHODS: We searched the National Inpatient Sample Database for hospitalized patients from 2003 to 2014 with a primary diagnosis of methanol intoxication. We excluded patients with end-stage kidney disease. We identified the AKI using a discharge diagnosis code. We compared clinical characteristics, in-hospital treatment, outcomes, and resource use between AKI and non-AKI patients. RESULTS: A total of 603 hospital admissions for methanol intoxication were analyzed. AKI developed in 135 (22.4%) admissions. Anemia (OR 3.43 p < 0.001), hypertension (OR 1.86; p = 0.02), volume depletion (OR 3.46; p = 0.001), sepsis (OR 6.91; p < 0.001), rhabdomyolysis (OR 6.25; p = 0.003), and acute pancreatitis (OR 5.30; p = 0.004) were independent risk factors for AKI development. AKI was significantly associated with increased risk of in-hospital mortality and organ failure. AKI patients needed more mechanical ventilation, and extracorporeal therapy, had longer length of hospital stay, and higher hospitalization costs. CONCLUSION: Over one-fifth of methanol intoxication patients developed AKI during hospitalization. AKI was associated with higher morbidity, mortality, and resource utilization.